On the origin of radiation-induced metastability in vitreous chalcogenide semiconductors: The role of intrinsic and impurity-related destruction-polymerization transformations - Shpotyuk, M.V.; Vakiv, M.M; Shpotyuk, O.I; Ubizskii, S.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Radiation-optical effects in vitreous chalcogenide semiconductors are comprehensively analyzed as resulting from both intrinsic and impurity-related redistribution of covalent chemical bonds known also together as destructionpolymerization transformations. Two types of experimental measuring protocols can be used to study radiation-induced effects within ex-situ direct or in-situ backward measuring chronology, the latter being more adequate for correct separated testing of competitive inputs from both channels of destruction-polymerization transformations. Critical assessment is given on speculations trying to ignore intrinsic radiation-structural transformations in As₂S₃ glass in view of accompanying oxidation processes. In final, this glass is nominated as the best model object among wide group of vitreous chalcogenide semiconductors revealing the highest sensitivity to radiation-induced metastability.